Angina pectoris in patients with HIV/AIDS: prevalence and risk factors - Zirpoli,Josefina Cláudia (2012)
INTRODUCTION: The incidence of ischemic heart disease is higher in patients with HIV/AIDS. However, the frequency of angina pectoris in these patients is still not known. Literature about this subject is still scarce. OBJECTIVE: To evaluate the prevalence of angina pectoris and risk factors for coronary disease and to examine the association between traditional risk factors and HIV-related risk factors and angina pectoris. METHOD: An epidemiological cross-sectional study, analyzed as case-control study, involving 584 patients with HIV/AIDS. Angina pectoris was identified by Rose questionnaire, classified as definite or possible. Information regarding risk factors was obtained through a questionnaire, biochemical laboratory tests, medical records and anthropometric measures taken during consultations at AIDS treatment clinics in Pernambuco, Brazil, from June 2007 to February 2008. To adjust the effect of each factor in relation to others, multiple logistic regression was used. RESULTS: There was a preponderance of men (63.2%); mean ages were 39.8 years for men, 36.8 years for women. The prevalence of definite and possible angina were 11% and 9.4%, respectively, totaling 20.4%, with independent associations between angina and smoking (OR = 2.88; 95% CI: 1.69-4.90), obesity (OR = 1.62; 95% CI: 0.97-2.70), family history of heart attack (OR = 1.70; 95% CI: 1.00-2.88), low schooling (OR = 2.11; 95% CI: 1.24-3.59), and low monthly income (OR = 2.93; 95% CI: 1.18-7.22), even after adjustment for age. CONCLUSION: This study suggests that angina pectoris is underdiagnosed, even in patients with medical monitoring, revealing lost opportunities in identification and prevention of cardiovascular morbidity.